KEKUATAN HUKUM SERTIFIKAT ELEKTRONIK SEBAGAI ALAT BUKTI DALAM SENGKETA JUAL BELI TANAH - Raffi Fikriansyah Lipurta; Suwarno Abadi (HUKMY : Jurnal Hukum, 2026)
The development of information technology in Indonesia has brought significant changes to the practice of land sale and purchase transactions, particularly through electronic mechanisms. Electronic certificates function as instruments for data and identity authentication, yet they also raise debates regarding their legal validity and position as evidence in land dispute cases. This study aims to examine the legal status of electronic certificates as valid evidence within Indonesia’s legal system and to assess their effectiveness in providing legal protection for parties engaging in digital transactions. The research method employed is a normative juridical approach by reviewing relevant regulations, including Law Number 11 of 2008 on Information and Electronic Transactions and its amendment through Law Number 19 of 2016, as well as implementing regulations concerning electronic certificates, namely Minister of Agrarian Affairs and Spatial Planning/National Land Agency Regulation Number 1 of 2021 and Ministerial Regulation Number 3 of 2023. In addition, this study is supported by secondary legal materials such as literature, academic journals, and previous research. The findings indicate that electronic certificates hold equal legal standing with conventional certificates, provided they comply with the principles of authentication, data integrity, and legal verification. Moreover, electronic certificates serve not only as proof of ownership but also as instruments for dispute prevention through an integrated digital system. Nevertheless, their implementation still faces challenges, including limited infrastructure, gaps in digital literacy, and public concerns regarding data security